PRIMARY PANCREATIC LYMPHOMA IN A YOUNG PATIENT WITH EARLY ONSET TYPE I DIABETES MELLITUS - Valentina Bozzoli; Francesco D'Alò; Maria Chiara Tisi; Giuseppina Massini; Dario Pitocco; Vittori Rufini; Maria Lucia Calcagni; Alberto Larghi; Luigi Maria Larocca; Luciana Teofili; Stefan Hohaus (Mediterranean Journal of Hematology and Infectious Diseases)
Primary pancreatic lymphoma (PPL) is an extremely rare disease which occurs in pancreas, and accounts for less than 1% of extra-nodal malignant lymphomas and 0,5% of cases of pancreatic masses. We report the case of PPL in a 15 year-old boy suffering from Type I Diabetes Mellitus (DM) diagnosed at the age of 1 year. The patient achieved complete remission by immuno-chemotherapy. An association between type I DM  and PPL has never been reported so far and could represent a new link between chronic autoimmune disease and primary extranodal lymphoma in a target tissue.